Virtual Learning Communities: A Tool to Foster Inclusion in the Teaching of English from Curricular Contextualization - Jiménez Porras, Karla (2015)
In Costa Rica, English teaching and learning have been considered a priority for decades, in order to help students face life and work situations which require an average command of English, with the desire that this preparation will allow them to participate actively into the challenges of the global economy. However, traditional teaching methods for language learning are implemented in the classrooms, limiting the acquisition of communicative skills in the students, which is more noticeable when those with Special Learning Needs walk into the regular classrooms. Inclusive practices become a must to promote every student’s success. A virtual learning community for teachers becomes a feasible tool to offer teachers with training to cater for the needs of those students.